2009
DOI: 10.1103/physrevlett.103.124501
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Disconnection of an Underwater Air Bubble: Persistent Neck Vibrations Evolve into a Smooth Contact

Abstract: The disconnection of an underwater bubble illustrates how slight initial asymmetries can prevent the formation of a finite-time singularity. Creating a singularity by focusing a finite amount of energy dynamically into a vanishingly small amount of material requires that the initial condition be perfectly symmetric. In reality, imperfections are always present. We show a slight azimuthal asymmetry in the initial shape of the bubble neck excites vibrations that persist over time. As a result, the focusing singu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 27 publications
2
45
0
Order By: Relevance
“…We find that the singularity (i) occurs at the film boundary, (ii) lacks the cylindrical symmetry found in the collapse of a catenoid (13), or even the bilateral symmetry recently observed in bubble pinch off (20), and changes the linking number between the Plateau border and the centerline of the wire frame, (iii) displays an intriguing crossover from a nonclassical behavior in the collapse of the film to the more familiar one arising from a balance of capillary forces and air inertia (15,21), and (iv) has energetics and geometry that may be understood through analysis of minimal surfaces and ruled surfaces spanning a family of parametrized frames (22).…”
mentioning
confidence: 92%
“…We find that the singularity (i) occurs at the film boundary, (ii) lacks the cylindrical symmetry found in the collapse of a catenoid (13), or even the bilateral symmetry recently observed in bubble pinch off (20), and changes the linking number between the Plateau border and the centerline of the wire frame, (iii) displays an intriguing crossover from a nonclassical behavior in the collapse of the film to the more familiar one arising from a balance of capillary forces and air inertia (15,21), and (iv) has energetics and geometry that may be understood through analysis of minimal surfaces and ruled surfaces spanning a family of parametrized frames (22).…”
mentioning
confidence: 92%
“…Instead, a variety of closure types arise (cf. Turitsyn et al 2009); for example: pointy and angular structures, finger-like forms, jets in the radial direction, and sub-cavities. Combinations of two or more of these events might take place.…”
Section: Effect Of Large-amplitude Disturbancesmentioning
confidence: 99%
“…If axial symmetry is broken by a small azimuthal perturbation, a truly universal system would be expected to converge to the same solution . However, through experiments and simulations of an air bubble disconnecting from an underwater nozzle, Keim, Møller, Zhang & Nagel (2006); Schmidt, Keim, Zhang & Nagel (2009) ;Turitsyn, Lai & Zhang (2009);and Keim (2011) recently showed that a slight azimuthal asymmetry can trigger vibrations that persist in time. The fact that a small perturbation is not smoothed out indicates that the system possesses memory of its initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This idea successfully describes several breakup scenarios, such as water drops break up in air [8][9][10][11][12] . However, recent studies reported that there are breakups which remember their initial states [13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%